The boys of summer [compact disc, unabridged] : the classic narrative of growing up within shouting distance of Ebbets Field, covering the Jackie Robinson Dodgers, and what's happened to everybody since - Kahn, Roger (Brilliance Audio, 2009)
Roger Kahn shares chronicles his life growing up near Ebbets Field. He also shares his experiences covering the Brooklyn Dodgers for the Herald Tribune.